Responses of different cucurbits stem cuttings to IBA (Indian Journal of Arid Horticulture, 2025)
An experiment was conducted to examine the efficacy of different doses of IBA (250 and 500 ppm) on stem cuttings of cucumber, sponge gourd and tinda commonly grown in Baran district of Rajasthan. The stem cuttings treated with 500 ppm IBA induced earlier, profuse rooting and maximum survival percentage than 250 ppm IBA and rainy season was found favourable for rooting in all cucurbits i.e. cucumber, sponge gourd and bitter gourd. Highest dose of IBA also produced maximum branching and takes one week lesser time to induce flowering and fruits were harvested slightly earlier than other treatment. Flower induction was slightly earlier in summer season than rainy season in all the cucurbits. The response of 500 ppm IBA was more effective to increased the yield (219.51-254.01 q/ha) in the entire cucurbit crop and harvested about one week earlier than other treatment.
Keywords: Cucurbits; cucumber; indole butyric acid; sponge gourd; stem cutting and tinda